How perception of environmental and social justice drive citizen's satisfaction and intention to engage with urban forests management? - Rahim Maleknia (Heliyon)
The equitable distribution of urban forests in cities and the inclusive consideration of all citizens' voices, regardless of their socioeconomic differences, are prime examples of social and environmental justice in urban areas. The citizens' perception of social and environmental justice can influence their satisfaction with urban forests and this satisfaction can, in turn, affect their intention to participate in the urban forests management. This study aimed to investigate the role of perceived environmental and social justices on citizens' satisfaction with urban forests and the impact of this satisfaction on their behavioral intention to engage in the urban forests management. A survey of 453 citizens was conducted to collect the data. Structural equation modeling was used to analyze the data. The results showed that the two variables of perceived environmental and social justice significantly influence citizens' satisfaction with urban forests, explaining 71 % of the variance in citizens' satisfaction. Furthermore, citizens' satisfaction, influenced by these two factors, had a positive and significant effect on their behavioral intention to participate in the management of urban forests, explaining 50 % of the behavioral intention. The findings highlight the importance of environmental and social justice in the distribution and management of urban forests. Attention to the equitable distribution and the inclusive consideration of all stakeholders in the management of these forests can facilitate citizens' engagement in the of urban forests management.